Sunflower Seed Oil Enriched with Phenolic Compounds from Barbatimão Bark - de Oliveira Cavitioli, Janiani; de Castro França, Izabelle Alves; Raspe, Djéssica Tatiane; Stevanato, Natália; dos Santos Garcia, Vitor Augusto [UNESP]; Barros, Beatriz Cervejeira Bolanho; da Silva, Camila (MDPI, 2025)
This study aimed to use sunflower seeds (SSs) and barbatimão bark (BB) to obtain an oil enriched with phenolic compounds. For this purpose, simultaneous extractions were carried out using different proportions of SSs and BB. Subsequently, the effects of temperature and extraction time were determined. The resulting oils were evaluated for composition and physicochemical properties. BB addition decreased the mass yield by 27% to 56% but increased the total phenolic content by 5 to 13 times. The best SS/BB ratio (3:2.5) was selected for further experiments. Increasing the extraction temperature from 30 to 60 °C and the extraction time from 15 to 60 min led to a 10% increase in oil yield and enhanced the contents of phenolic acids and flavonoids by 1.1 to 10 times. Gallic, quinic, and trans-cinnamic acids were the main phenolics in enriched oils, which exhibited higher antioxidant activity via the DPPH•, FRAP, and ABTS•+ methods. Linoleic and oleic acids were identified as the major fatty acids in the tested oils. Enriched oils showed greater thermal stability than their unenriched counterpart. The application of phenolic-enriched oil at concentrations of up to 400 µg/mL did not exert cytotoxic effects on human keratinocyte HaCaT cells.